Japan: The "Haves" are Gaining and the "Have-Nots" are Losing - Obara, Yoshiaki (International Higher Education, 2009)
Many Japanese private higher education institutions also face a risk of falling into the "losing group." It seems that small/rural colleges end up receiving less extra income from admissions over the tei-in (the quota for first-year students) level. This loss creates less scholarship money for capable students. The small/rural institutions are likely to lose prospective students as a negative cycle works against them. This tendency, in turn, augments the opportunities available to large, metropolitan higher education institutions. In Japan, a clear division is anticipated, with the larger institutions getting much larger and the smaller and rural ones getting much smaller. This is a hard fact that we will face in the foreseeable future.